E-Commerce: A Case Study Of The Malaysian Goverment E-Procurement Project - Shamsudin, Fazida Akmal (2002)
The purpose of this research is to explore the issues on the implementation of Electronic Procurement (E-procurement) initiated by the goverment of Malaysia. This project is also aimed at bringing about additional knowledge on this subject. Thus, this research study aims to clarify the whether the E-Procurement project is a good investment or vice versa. The areas of interest inclusive of the benefits, problems, level of demand and readiness, strenghts, weaknesses, opportunities, threats, and some other related issues.